Influence of Product Quality, Service Quality and Completeness on Customer Satisfaction on Mie Soponyono Producer - Zakirin, Mamduhan (International Journal of Review Management Business and Entrepreneurship (RMBE), 2021)
Mie Soponyono Manufacturer is a company engaged in the food and beverage sector, which is precisely producing wet noodles and dumpling skin. The purpose of this study was to see the effect of product influence, service quality and completeness on customer satisfaction. The population in this study were subscribers of the Mie Soponyono producers. Determination of the sample in this study using purposive sampling. This study uses multiple linear regression analysis. The results of this study indicate that product quality has no effect on customer satisfaction, service quality affects customer satisfaction and product completeness affects customer satisfaction. Variables of product quality, service quality, and product completeness contributed to customer satisfaction by 70%, while the rest could be built by other variables.